General visualization of dynamic capabilities: based on a bibliometric analysis (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2023)
The scientific production related to dynamic capacities is analyzed through the bibliometric analysis carried out from documents retrieved from the SCOPUS database corresponding to the period 2017-2020, implementing a quantitative methodology of co- words and in the representation of the relationships between words or terms through bibliometric maps using the VOSviewer software. The completion of the improved study resulted in visualizations of thematic structures in the research areas of dynamic capacities, allowing the identification of nine (9) clusters that define the main research currents. The maps reveal that, in the period analyzed, there is a consolidated macro-line of research, which includes studies on dynamic capacity, adaptability, integration, reconfiguration, strategy, strategic planning, teamwork, transformation, absorption capacity, adaptability, capacity innovation, financial performance, new product development, organizational culture, productivity, resilience, flexibility strategy, among others; However, globally, especially in Latin America, there is an incipient investigation regarding specific Dynamic Capacities; in this case those related to the management of human talent. Likewise, a consolidated research axis has been identified in management sciences. A future construction of bibliometric maps is proposed, with other databases in a comparative way that allow analyzing the CDs from their constituent elements, as well as their evolution
Keywords: dynamic capabilities; bibliometrics; cluster